2014
DOI: 10.3390/soc4040737
|View full text |Cite
|
Sign up to set email alerts
|

Eating Animals to Build Rapport: Conducting Research as Vegans or Vegetarians

Abstract: Notions of hospitality, community, and the fostering of rapport and connection are foundational concerns for conducting research across difference. Drawing on methodological literature, this paper considers how access to various communities and "good" data is structured by the notion that in order to develop rapport researchers accept the "food", specifically "meat" offered by their hosts. When researchers are vegetarians or vegans, this can entail a conflict in which questions of hospitality, relationships, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The goal of the interviews was to elicit rich first-person descriptions of vegans' lived experiences. At the beginning of the interviews, the researcher identified herself as a vegan, in order to build a rapport with the interviewees and create a trust relationship [57,58]. The interviews began with narrative background information, with respondents being asked to explain: (1) Their backgrounds and their vegan lifestyle choices, (2) what they liked about being vegan, in general and in relation to food, and (3) whether they felt that the pleasure deriving from food-related experiences (shopping, cooking, eating) were facilitated or hampered by any factors and, if so, which ones.…”
Section: Methodsmentioning
confidence: 99%
“…The goal of the interviews was to elicit rich first-person descriptions of vegans' lived experiences. At the beginning of the interviews, the researcher identified herself as a vegan, in order to build a rapport with the interviewees and create a trust relationship [57,58]. The interviews began with narrative background information, with respondents being asked to explain: (1) Their backgrounds and their vegan lifestyle choices, (2) what they liked about being vegan, in general and in relation to food, and (3) whether they felt that the pleasure deriving from food-related experiences (shopping, cooking, eating) were facilitated or hampered by any factors and, if so, which ones.…”
Section: Methodsmentioning
confidence: 99%
“…Denzin and Lincoln, 1998). More recent literature has suggested that disagreement can be imagined as useful in the field (MacDonald and Montford, 2014;Smyth and Mitchell, 2008).…”
Section: On Being In Relationmentioning
confidence: 99%